Effectiveness of Purpose-Oriented Counseling on Postpartum Contraceptive Decision-Making Among Women - Pratiwi, Iva Gamar Dian; Permatasari, Dian; Huzaimah, Nailiy; Fatoni, Akhmad Feri; Rahmawati, Sylvina (International Journal of Health Concord, 2025)
Background: Postpartum contraception is essential for ensuring safe birth spacing and reducing maternal-infant morbidity. However, decision-making regarding contraceptive use remains suboptimal due to inadequate and generalized counseling. This study aimed to evaluate the effectiveness of the One-Purpose Counseling Technique in improving postpartum women's decisions on appropriate contraceptive selection. Methods: A pre-experimental post-test-only control group design was used, involving 40 postpartum women within 40 days of delivery. Participants were divided into two groups: 20 received structured One-Purpose Counseling and 20 received standard counseling. Data were collected at the Pamolokan Community Health Center and analyzed using chi-square and independent samples t-test with SPSS 26. Result: Among women who received One-Purpose Counseling, 75% selected an appropriate contraceptive method, compared to only 15% in the control group. The difference was statistically significant (p = 0.00047), indicating a strong effect of the intervention on informed contraceptive decision-making. Conclusion: The One-Purpose Counseling Technique significantly enhances postpartum women's ability to choose suitable contraception by focusing on goal-oriented, personalized interaction. Health practitioners, especially in low-resource settings, are recommended to adopt this model to improve contraceptive uptake and reproductive autonomy. Future research should assess long-term contraceptive adherence and satisfaction following this intervention.